Training Kit Exam 70-462 : administering Microsoft SQL Server 2012 databases - Thomas, Orin, 1973- (Microsoft Press, 2012)
EXAM PREP GUIDE Ace your preparation for the skills measured by Exam 70-462—and on the job—with this official Microsoft study guide. Work at your own pace through a series of lessons and reviews that fully cover each exam objective. Then, reinforce and apply what you've learned through real-world case scenarios and practice exercises. Maximize your performance on the exam by mastering the skills and experience measured by these objectives: Install and configure SQL Server Maintain instances and databases Optimize and troubleshoot SQL Server Manage data Implement security Implement high availability PRACTICE TESTS A Note Regarding Practice Tests Assess your skills with practice tests. You can work through hundreds of questions using multiple testing modes to meet your specific learning needs. You get detailed explanations for right and wrong answers—including a customized learning path that describes how and where to focus your studies. For customers who purchase an ebook version of this title, instructions for downloading the CD files can be found in the ebook.